Development of an ionic-liquid-based dispersive liquid-liquid microextraction method for the determination of antichagasic drugs in human breast milk: Optimization by central composite design - Padró, Juan Manuel (2015)
Chagas disease constitutes a major public health problem in Latin America. Human breast milk is a biological sample of great importance for the analysis of therapeutic drugs, as unwanted exposure through breast milk could result in pharmacological effects in the nursing infant. Thus, the goal of breast milk drug analysis is to inquire to which extent a neonate may be exposed to a drug during lactation. In this work, we developed an analytical technique to quantify benznidazole and nifurtimox (the two antichagasic drugs currently available for medical treatment) in human breast milk, with a simple sample pretreatment followed by an ionic-liquid-based dispersive liquid-liquid microextraction combined with high-performance liquid chromatography and UV detection. For this technique, the ionic liquid 1-octyl-3-methylimidazolium hexafluorophosphate has been used as the "extraction solvent." A central composite design was used to find the optimum values for the significant variables affecting the extraction process: volume of ionic liquid, volume of dispersant solvent, ionic strength, and pH. At the optimum working conditions, the average recoveries were 77.5 and 89.7%, the limits of detection were 0.06 and 0.09 μg/mL and the interday reproducibilities were 6.25 and 5.77% for benznidazole and nifurtimox, respectively. The proposed methodology can be considered sensitive, simple, robust, accurate, and green.